New shoes - Raschka, Christopher (Greenwillow, an imprint of HarperCollinsPublishers, 2018)
When a young child discovers a hole in a sneaker, mother and child embark on a big childhood adventure--a trip to the store to pick out new shoes. From having feet measured and making a selection to finally showing off the new shoes to a friend, this momentous child moment is treated with respect, excitement, and page-turning energy in a wonderfully age-appropriate picture book.--Amazon.com.